2013
DOI: 10.1093/ehjci/jes323
|View full text |Cite
|
Sign up to set email alerts
|

Speckle-tracking strain of the left atrium: a transoesophageal echocardiographic validation study

Abstract: Assessment of LA mechanical function using speckle-tracking echocardiography is a valid approach compared with transoesophageal echocardiography, and is clinically feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…A study using tissue Doppler imaging has shown a moderately strong positive association (r = 0.73; p = 0.007) between mean left atrial systolic strain and LAA appendage emptying velocities [28], contrary to what we found in our sample. Leong et al have found that speckle tracking derived parameters are more rapidly measured and more accurate than tissue Doppler for the discrimination of the presence of moderate-severe left atrial spontaneous echocardiographic contrast [29]. Patients with AF are also known to present higher degrees of left atrial dyssynchrony [30].…”
Section: Discussionmentioning
confidence: 99%
“…A study using tissue Doppler imaging has shown a moderately strong positive association (r = 0.73; p = 0.007) between mean left atrial systolic strain and LAA appendage emptying velocities [28], contrary to what we found in our sample. Leong et al have found that speckle tracking derived parameters are more rapidly measured and more accurate than tissue Doppler for the discrimination of the presence of moderate-severe left atrial spontaneous echocardiographic contrast [29]. Patients with AF are also known to present higher degrees of left atrial dyssynchrony [30].…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of LA mechanics is a recent field of study, and many novel methods for assessment of LA motion parameters have been developed. Recent evidence has suggested that LA mechanics measurement by speckle tracking echocardiography might have a promising role in the assessment of LA function and as a predictor of ischemic stroke …”
mentioning
confidence: 99%
“…86 The degree of atrial fibrosis as assessed by late gadolinium enhancement on MRI has been associated with the presence of LAA thrombi and spontaneous contrast, 87 as has left atrial dysfunction identified by strain imaging which identifies abnormalities in myocardial deformation. 88,89 Bipolar voltage mapping of the left atrium in AF has correlated the extent of myopathic low voltage electrograms (≤0.5 mV) with reduced LAA emptying velocity. 90 These tissue changes have been proposed to contribute to increased local thrombogenicity at the blood-endocardium interface.…”
Section: Left Atrial Appendage Dysfunction and Myopathymentioning
confidence: 99%